THE INFLUENCE OF INSTAGRAM ADVERTISING AND DIGITAL TECHNOLOGY ON BRAND AWARENESS AND PURCHASE DECISIONS IN THE ERA OF SOCIETY 5.0 - Irene, Novi; Listiana, Erna; Barkah, Barkah; Fitriana, Ana; Setiawan, Harry (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The goal of this study is to investigate how, in the era of Society 5.0, digital marketing strategies affect Maybelline lipstick product purchases in Indonesia. The main focus of this study is on how Instagram advertising and digital technologies affect customer purchasing decisions and increase brand recognition. Purposive sampling was used to select 300 respondents, who were then surveyed to collect quantitative data. The data was examined using Structural Equation Modeling (SEM). The results showed that Instagram ads and digital technology significantly improve brand recognition, which influences customer purchasing decisions. These findings show how effective digital marketing strategies are at increasing sales of cosmetics, especially in the context of changing customer behavior in the Society 5.0 era.